A Middleware Applications Design for Health Information Sharing - Seputra, Ketut Agus; Paramartha, A.A. Gede Yudhi; Pradnyana, Gede Aditra; Aryanto, Kadek Yota Ernanda (Jurnal RESTI (Rekayasa Sistem dan Teknologi Informasi), 2024)
The interoperability between electronic health records (EHR) and electronic medical records (EMR) from various healthcare facilities for comprehensive patient care is important. However, integrating such systems, including the need for interoperability standards, data privacy, and security, is a highly challenging task, especially since patient rights in data access must be considered. The primary problem addressed is the challenge of integrating electronic health records (EHR) and electronic medical records (EMR) within various healthcare facilities to ensure comprehensive patient care while maintaining data privacy, security, and adherence to patient rights. This work presents an innovative application for consolidating patient health records from various medical facilities. Facilitates seamless data access, improving the efficiency of healthcare care delivery. The GGD approach was used in developing the prototype to ensure that the delivered product was able to meet the user requirements. Four phases are divided into six stages used in this method: research, modeling, requirements definition, framework definition, refinement, and support. The evaluation involved two phases, back-end and front-end testing, using white-box and black-box testing. White-box testing delivers an average frame-rendering rate of up to 56 fps, and black-box testing has shown 100% successful results in the given task. In conclusion, the Med-OID prototype was successfully developed. Integrates and securely transmits medical records across various healthcare services, demonstrating significant potential to enhance personalized medicine and healthcare coordination. The evaluations underscored the robustness of the prototype and its ability to improve interoperability and data sharing in healthcare systems.